Ionizing Radiation, Higher Plants, and Radioprotection: From Acute High Doses to Chronic Low Doses - Caplin, Nicol; Willey, Neil (Frontiers in Plant Science, 2018)
Understanding the effects of ionising radiation (IR) on plants is important for environmental protection, for agriculture and horticulture, and for space science but plants have significant biological differences to the animals from which much relevant knowledge is derived. The effects of IR on plants are understood best at acute high doses because there have been; a) controlled experiments in the field using point sources, b) field studies in the immediate aftermath of nuclear accidents, and c) controlled laboratory experiments. A compilation of studies of the effects of IR on plants reveals that although there are numerous field studies of the effects of chronic low doses on plants, there are few controlled experiments that used chronic low doses. Using the Bradford-Hill criteria widely used in epidemiological studies we suggest that a new phase of chronic low-level radiation research on plants is desirable if its effects are to be properly elucidated. We emphasise the plant biological contexts that should direct such research. We review previously reported effects from the molecular to community level and, using a plant stress biology context, discuss a variety of acute high- and chronic low-dose data against Derived Consideration Reference Levels (DCRLs) used for environmental protection. We suggest that chronic low-level IR can sometimes have effects at the molecular and cytogenetic level at DCRL dose rates, and perhaps below, but that there are unlikely to be environmentally significant effects at higher levels of biological organisation. We conclude that, although current data meets only some of the Bradford-Hill criteria, current DCRLs for plants are very likely to be appropriate at biological scales relevant to environmental protection (and for which they were intended) but that research designed with an appropriate biological context and with more of the Bradford-Hill criteria in mind would strengthen this assertion. We note that the effects of IR have been investigated on only a small proportion of plant species and that research with a wider range of species might improve not only the understanding of the biological effects of radiation in general but also that of the response of plants to environmental stress.